PELATIHAN DASAR KEWIRAUSAHAAN BERBASIS TEKNOLOGI INFORMASI DI SMKN 2 DENPASAR - Juliharta, I Gede Putu Krisna; Astawa, Ni Luh Putu Ning Septyarini Putri; Fredlina, Ketut Queena; Dewi, Putri Anugrah Cahya; Zildjian, Romiza; Suartama, I Komang (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
The digital era, opportunities for students to learn about entrepreneurship. With the advent of information technology such as smartphones and laptops, starting entrepreneurial activities has become more accessible for students. SMKN 2 Denpasar is one of the schools implementing and supporting entrepreneurship education. This program aims to instil an entrepreneurial spirit in students and enhance their foundational business knowledge and mindset on starting a business from scratch. The methods used in this program include imparting an entrepreneurial mindset, utilising the Business Model Canvas (BMC) to analyse and plan business models, managing business finances to effectively control financial resources, and creating digital content for marketing through social media. The results indicate that students responded positively and found the entrepreneurship learning beneficial, as evidenced by the questionnaires completed by students regarding the IT-based entrepreneurship training they participated in.